Angiotensin II Type 1A Receptor Expressed in Smooth Muscle Cells is Required for Hypertensive Vascular Remodeling in Mice Infused With Angiotensin II. Issue 3 (11th January 2023) - Okuno, Keisuke; Torimoto, Keiichi; Cicalese, Stephanie M.; Preston, Kyle; Rizzo, Victor; Hashimoto, Tomoki; Coffman, Thomas M.; Sparks, Matthew A.; Eguchi, Satoru
Abstract : Background: Ang II (angiotensin II) type 1 (AT1 ) receptors play a critical role in cardiovascular diseases such as hypertension. Rodents have 2 types of AT1 receptor (AT1A and AT1B ) of which knock-in Tagln -mediated smooth muscle AT1A silencing attenuated Ang II–induced hypertension. Although vascular remodeling, a significant contributor to organ damage, occurs concurrently with hypertension in Ang II–infused mice, the contribution of smooth muscle AT1A in this process remains unexplored. Accordingly, it is hypothesized that smooth muscle AT1A receptors exclusively contribute to both medial thickening and adventitial fibrosis regardless of the presence of hypertension. Methods: About 1 µg/kg per minute Ang II was infused for 2 weeks in 2 distinct AT1A receptor silenced mice, knock-in Tagln -mediated constitutive smooth muscle AT1A receptor silenced mice, and Myh11 -mediated inducible smooth muscle AT1A together with global AT1B silenced mice for evaluation of hypertensive cardiovascular remodeling. Results: Medial thickness, adventitial collagen deposition, and immune cell infiltration in aorta were increased in control mice but not in both smooth muscle AT1A receptor silenced mice. Coronary arterial perivascular fibrosis in response to Ang II infusion was also attenuated in both AT1A receptor silenced mice. Ang II–induced cardiac hypertrophy was attenuated in constitutive smooth muscle AT1A receptor silenced mice. However, Ang II–induced cardiac hypertrophy and hypertension were not altered in inducible smooth muscle AT1A receptor silenced mice. Conclusions: Smooth muscle AT1A receptors mediate Ang II–induced vascular remodeling including medial hypertrophy and inflammatory perivascular fibrosis regardless of the presence of hypertension. Our data suggest an independent etiology of blood pressure elevation and hypertensive vascular remodeling in response to Ang II.